বাংলাদেশের উন্নয়ন কি অসম্ভব? : অস্থায়ী সরকার গঠিত ২৯টি টাস্কফোর্স রিপোর্টের পর্যালোচনা - মুহাম্মদ, আনু (ঢাকা : জাতীয় গ্রন্থ প্রকাশন, 1995)
Survey on reports of the task forces on Bangladesh development strategies for 1990s.
In Bengali.
Includes bibliographical references (p. 117-120).
Keywords: Economic development projects -- Bangladesh; Bangladesh -- Economic policy